2014
DOI: 10.1186/1748-717x-9-134
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol and radiotherapy-induced carotid atherosclerosis in subjects with head and neck cancer

Abstract: BackgroundRadiotherapy (RT) is a risk factor for accelerated carotid artery atherosclerotic disease in subjects with head and neck cancer. However, the risk factors of RT-induced carotid artery remodeling are not established. This study aimed to investigate the effects of RT on carotid and popliteal arteries in subjects with head and neck cancer and to evaluate the relationship between baseline clinical and laboratory features and the progression of RT-induced atherosclerosis.FindingsEleven men (age = 57.9 ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Our findings are thus consistent with previous reports of an association between baseline cholesterol levels and increases in the intima-media thickness (IMT) or plaque scores as measured by duplex sonography. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are thus consistent with previous reports of an association between baseline cholesterol levels and increases in the intima-media thickness (IMT) or plaque scores as measured by duplex sonography. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future work should investigate whether statins or other drugs protect the carotid arteries from RT‐related injury. The hypothesis that statins reduce RT‐related carotid artery injury by lowering cholesterol levels is suggested by a clinical study that found that the degree of progression in carotid artery intima‐media thickness after RT was associated with pre‐RT low‐density lipoprotein cholesterol levels ( r = 0.66; p = 0.03) . If statins are found to be protective, this would lead to an expansion of the indications for statin use to include patients receiving head and neck RT with otherwise low CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Every effort to mitigate IS occurrence and the progression of post-RT vasculopathy in HNC survivors is crucial [29]. However, in the early post-RT vasculopathy phase, few interventions had been proved effective in curbing or slowing down disease progression [30][31][32][33][34]. In our results, thyroxine supplement showed insu cient clinical bene ts on CAS progression or IS prevention in HNC patients after RT.…”
Section: Discussionmentioning
confidence: 54%